"The Return of Big Government--Policy Advice for President Obama" - L. Randall Wray
In the current global financial crisis, economists and policymakers have reembraced Big Government as a means of preventing the reoccurrence of a debt-deflation depression. The danger, however, is that policy may not downsize finance and replace money manager capitalism. According to Senior Scholar L. Randall Wray, we need a permanently larger fiscal presence, with more public services. His advice to President Obama is to discard all of former Treasury Secretary Paulson's actions. Wray believes that we can afford any necessary spending and bailouts, and that these actions will not burden our grandchildren.